Factors Governing the Catalytic Insertion of CO2 into Arenes – A DFT Case Study for Pd and Pt Phosphane Sulfonamido Complexes. Issue 23 (21st March 2022) - Hölscher, Markus; Kemper, Gregor; Jenthra, Sangeth; Bolm, Carsten; Leitner, Walter
Abstract: The potential of Pd/Pt complexes for catalytic carboxylation of arenes with CO2 is investigated by means of computational chemistry. Recently we reported that the bis[(2‐methoxyphenyl)phosphino]‐benzenesulfonamido palladium complex 1 inserts CO2 reversibly in its Pd−C(aryl) bond generating carboxylato complex 2 . In the present work we study how geometric and electronic factors of various ligands and substrates influence the overall activation barrier (energy span, ES) of a potential catalytic cycle for arene carboxylation comprising this elementary step. The tendency of the key intermediates to dimerize and thus deactivating the potential catalysts is examined as well as the role of the base, which inevitably is needed to stabilize the reaction product. We show that Pd and Pt complexes I(Pd) ‐L16 ‐S1 and I(Pt) ‐L16 ‐S1 do not dimerize, enable the computation of complete catalytic cycles, and show interestingly low ES values of 26.8 and 24.5 kcal/mol, respectively. Abstract : Which catalyst does the job ? A DFT based catalyst screening with Pd/Pt complexes for the catalytic direct insertion of CO2 into the C−H bonds of arenes to provide a carbonic acid indicates that a catalytic process might well be achievable, when the multi‐parameter system is carefully tuned. Not only the choice of metal is important, also the size and shape as well as the electronic influences of the ligand and the electronic influences of the substrate needs to be concerned. The appropriate base also must be found and some undesired side reactions must be suppressed.